“Let the Sirens Roar”: The Women’s Protests in Poland and the Artistic Response to the Backlash - Małgorzata Stępnik (Slavia Meridionalis, 2022)
“Let the Sirens Roar”: The Women’s Protests in Poland and the Artistic Response to the Backlash